Saliva as a Candidate for COVID-19 Diagnostic Testing: A Meta-Analysis - Czumbel, László Márk; Kiss, Szabolcs; Farkas, Nelli; Mandel, Iván; Hegyi, Anita; Nagy, Ákos; Lohinai, Zsolt; Szakács, Zsolt; Hegyi, Péter; Steward, Martin C.; Varga, Gábor (Frontiers in Medicine, 2020)
Background: COVID-19 is a serious and potentially deadly disease. Early diagnosis of infected individuals will play an important role in stopping its further escalation. The present gold standard for sampling is the nasopharyngeal swab method. However, several recent papers suggested that saliva-based tests are a promising alternative to simplify and accelerate COVID-19 diagnosis. Objectives: Our aim was to conduct a meta-analysis on the reliability and consistency of SARS-CoV-2 viral RNA detection in saliva specimens. Methods: We reported our meta-analysis according to the Cochrane Handbook. We searched the Cochrane Library, Embase, Pubmed, Scopus, Web of Science and clinical trial registries for eligible studies published between 1 January and 25 April 2020. The number of positive tests and total number of conducted tests were collected as raw data. The proportion of positive tests in the pooled data were calculated by score confidence interval estimation with the Freeman-Tukey transformation. Heterogeneity was assessed using the I2 measure and the 𝝌2 test. Results: The systematic search revealed 96 records after removal of duplicates. 26 records were included for qualitative analysis and 5 records for quantitative synthesis. We found 91% (95%CI = 80%-99%) sensitivity for saliva tests and 98% (95%CI 89%-100%) sensitivity for nasopharyngeal swab (NPS) tests in previously confirmed COVID-19 infected patients, with moderate heterogeneity among studies. Additionally, we identified 18 registered, ongoing clinical trials on saliva-based tests for detection of the virus. Conclusion: Saliva tests offer a promising alternative to NPS for COVID-19 diagnosis. However, further diagnostic accuracy studies are needed to improve their specificity and sensitivity.